What determines tourism loyalty?: The role of trust in online purchases of tourism products - Pereira, H. G.; Salgueiro, M. F. (European Academy of Management Conference, EURAM 2019, 2019)
The purpose of this research is to investigate the impact of four online purchase determinants(website image perceptions, online routine, website knowledge and innovativeness) on customer loyalty and the mediating effect of customer trust within the context of e-commerce. The research model is tested using data collected from 3188 regular buyers of the national leader in the sector being studied. The statistical analyses were conducted within the Structural Equation Modelling framework. Results show that there is no mediating effect of e-customer trust in the relationship between the online purchase determinants and e-customer loyalty. The research results provide an important insight into how e-companies can pursuit and use delight to highlight customers’ loyalty.These results allow for a better understanding of customer specificities, with practical actions aimed at their real needs and expectations.